Internal Nitrogen Pools Shape the Infection of Aureococcus anophagefferens CCMP 1984 by a Giant Virus - Gann, Eric R.; Hughes, Brennan J.; Reynolds, Todd B.; Wilhelm, Steven W. (Frontiers in Microbiology, 2020)
The pelagophyte Aureococcus anophagefferens blooms annually in shallow bays around the world, where it is hypothesized to outcompete other phytoplankton in part by using alternative nitrogen sources. The high proportion of natural populations that are infected during the late stages of the bloom suggest viruses cause bloom collapse. We hypothesized that the Aureococcus anophagefferens virus (AaV) infection cycle would be negatively influenced in cultures acclimated to increasingly limiting nitrogen conditions, but that the real-time external nitrogen concentration would not influence the infection cycle. Cultures acclimated in NO3- concentrations (0.0147 mM; N:P = 0.1225) that showed reduced end point cell abundances, forward scatter (a proxy for size), red fluorescence (a proxy for chlorophyll), and also produced less viruses per cell at a slower rate. Decreasing the external concentration of nitrogen after infection did not influence burst size or time to lysis. These data suggest that all the nitrogen required for new progeny is found within the host cells and is recycled. Flow cytometric data of the infection cycle showed a reduction in red fluorescence around twelve hours post infection, consistent with degradation of nitrogen-rich chloroplasts during the infection cycle. Using cell and virus quota estimates, we determined that Aureococcus cells had enough nitrogen and carbon for the estimated lower burst sizes, but did not contain enough phosphorous. Consistent with this observation nitrate and sugar transporters were not over expressed in the publicly available transcriptome data of the infection cycle, while several phosphorus transporters were. Our data demonstrate that dynamics of viruses infecting Aureococcus over the course of a bloom is dictated by the host cell state upon infection, which is set a priori by external nutrient supplies.